Detecção de espécies do vírus das estrias da bananeira (BSV) em Musa spp - Caldas, Camila Nogueira Pestana (2019)
In Brazil, the optimal climate conditionsenable banana production in the entire country. However, some phytopatogens such as fungi, nematodes, insects and vírus compromise yield and fruit quality. Among the vírus diseases, banana streak vírus (BSV) is the most important, whereas more than fifteen different species have been identified worldwide. The objectives of the present study were to identify BSV species in germplasm bank of Embrapa and in different banana production regions in Brazil by molecular characterization and indexation using IC-PCR(Immunocapture-PCR) + DNase, as well as map the presence of infective fragments in commercial germplasm and those of genome BB used in the crosses. Leaves of 300 banana accessions from the Embrapa ex situ germplasm collection and 39in vitro samples, were collected. Two-hundred and twenty-seven samples from eight different banana production regions in Brazil, were also collected. Twenty-three species-specific primers for detection of endogenous BSV (eBSV) for species Goldfinger(eBSGFV), Imovè (eBSIMV) and Obinol'Ewai (eBSOLV) were also used for the analysis of incidence and prevalence of viral species. The analysis of the 300 accessions of BAG showed that most samples were negative for eBSV and of the positive banana samples for eBSV, 20 were infected by episomal BSV of the BSOLV and BSGFV species. None of the analyzed samples contained BSV episomal of the BSIMV species. Most of the samples analyzed from the eight different banana producing regions in Brazil was positive for the presence of at least one of the eBSV species and only samples from the State of São Paulo and one from Santa Catarina presented episomal BSV. The study with hybrids developed by Embrapa identified presence of the infective fragment GF7 associated to the BSGFV species. Regarding the presence of the infective fragment associated to the BSOLV species, only the Thap Maeo cultivar was positive. The other genotypes amplified only the non-infective fragment, OL2. All eight accessions with BB genome presented either the infective fragment for the BSOLV species as well as for the BSGFV species. The IC-PCR + DNAse indexation confirmed the low presence of episomal BSV in the analyzed samples.